A framework for developing culture-based multi-modal mind games: improving social interaction skills of autistic children - Mohd Hanifa, Rafizah; Bahrudin, Ida Aryanie; Surip, Miswan; Ibrahim, Zuraida; Roslan, Rosfuzah; Alias, Maizam (Penerbit UTM Press, 2015)
Cases of autism, a developmental disorder that disconnects individuals from their environment and people is on the rise with 30% increase being reported in Malaysia from 2008-2011. Early childhood intervention is essential in ensuring autistic children have the opportunity to develop their full potential and enabling them to contribute to society in later years. The intervention will also enhance education opportunities of such children, thus supporting the efforts of NASOM as well as the government’s “education for all aspirations”. One approach that has shown great potential in enhancing social interaction skills among autistic children is the multi-modal mind games approach. The purpose of this paper is to present a framework in designing a culture-based multimedia supported mind games for autistic children. Action research method will be adopted since the cyclic nature of the method will provide opportunity for improving existing educational practices for autistic children. Needs analysis will be conducted to determine weaknesses and strengths of the current practices in developing social interaction skills among autistic children. Parents and teachers will be interviewed and autistic children between the age of five and eight will be observed to get a comprehensive view of the existing situation. Based on the analysis, a set of culture-based mind games multimedia supported as well as face to face interactions will be designed and prescribed to selected autistic children